Corporate life cycle, corporate governance structure, and corporate social responsibility disclosure - Permata Ayu Widyasari; Christian Sutanto; Maria Eugenia Hastuti (Jurnal Keuangan dan Perbankan, 2019)
The existence of Law No. 40/2007 concerning Limited Liability Company (or UU PT) in Indonesia can be an external motivation of the companies to ensure the conduct of corporate social responsibility (CSR) activities. In addition, the internal factor of the company can both drive and inhibit the conduct of CSR activities, such as the corporate life cycle. This study aims to determine the effect of the corporate life cycle, board of commissioners, and board of directors toward the disclosure of corporate social responsibility activities in manufacturing companies listed in Indonesian Stock Exchange. The corporate life cycle is categorized into five stages, including introduction, growth, maturity, decline, and shake-out. To accommodate the possibility of a non-linear corporate life cycle stage, the study employed multiple linear regressions and ANOVA analysis. The results showed that the corporate life cycle and board of commissioners have a significant effect on the disclosure of corporate social responsibility; while the board of directors has no effect on the disclosure of corporate social responsibility. The control variables used in this research include profitability, firm size, slack, research and development, market-to-book ratio, and firm age.JEL Classification: M12, M14, M41DOI: https://doi.org/10.26905/jkdp.v23i3.2694